An extreme physical reaction in misophonia: stop smacking your mouth! - Serhat Tunç; Hamit Serdar Başbuğ (Psychiatry and Clinical Psychopharmacology, 2017)
Misophonia is described as a condition in which negative emotions and negative physical reactions are triggered by particular sounds. The patients with misophonia demonstrate hatred and extreme intolerance against specific non-dominant and repetitive sounds. It is a severe psychiatric disorder rather than a mere obsession. Its symptoms may vary from mild to severe. Although some patients can dissemble and passed out, some may lose their control. In severe cases, involuntary physical violence may be observed. Although it is usually perceived as a spoil by the society, it may cause the patient’s life become unbearable. In this paper, the physical violence of a misophonia patient directed to a dinner guest who smacks his mouth during eating was reported. Unfortunately, the patient could not achieve to exclude himself from the source of disturbance before exhibiting the adverse physical reaction. Therefore, this case becomes important in demonstrating the extreme involuntarily reactive nature of misophonia.